Linguistic Analysis of Dove Indonesia’s Website and Its Localization - Evita Husodo; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2023)
This paper analyzes the website localization of Dove Indonesia’s website. The study, then, analyzes the adaptation and the translation technique of the translation part that includes the home page and its first next link of the website. In analyzing website localization, the theories that are used are the theory of website localization by Pym (2012) and the translation technique by Molina and Albir (2002). This study found that the website is highly localized with both adaptation and translation. Adaptation includes changes in data and time format, legal inventions, and content. The translation itself uses single and duplet translation techniques. Single technique includes amplification, borrowing, compensation, discursive creation, generalization, literal translation, modulation, particularization, reduction, and transposition. Duplet technique includes compensation and borrowing and reduction and amplification. However, the mostly used translation technique is a single technique, literal translation.